ANALYTICAL ASSURANCE OF PLANNING OF PRODUCT INNOVATION POLICY OF INDUSTRIAL ENTERPRISES IN THE CONDITIONS OF TECHNOLOGICAL WAYS TRANSFORMATION - ILLIASHENKO, SERGII; SHYPULINA, YULIIA; ILLIASHENKO, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In periods of technological transformation, innovations and innovative activity are an effective method to ensure the conditions for sustainable survival and development of industrial enterprises. Consequently, perspective strategic directions of innovative development and operative planning need to be defined primary in their product innovation policy as the pricing, communicative and sales policies are derived from it. An approach to the analytical support of planning the product innovation policy of an industrial enterprise in the constantly changing environmental conditions caused by the processes of transformation of technological systems has been developed. In contrast to existing approaches, it provides an analysis of trends in global and industry science and technology, the results of which can be used in production and marketing activities of the enterprise, in particular in forming a portfolio of product innovations as a means of adapting to changes in external micro and macro environment. Factors influencing the innovative development of industrial enterprises in general and their product innovation policy in particular are specified. The scheme of interaction of the specified factors in the course of analytical support of a product innovation policy of the industrial enterprise is outlined. Methodological bases of analytical planning of product innovation policy of industrial enterprises in conditions of technological ways transformation are developed. The application of the developed approach in innovative activities of industrial enterprises will allow purposefully and reasonably plan their product innovation policy as a basis for innovative development in conditions of technological ways transformation and the deployment of the 4th industrial revolution. The obtained scientific results deepen the methodological principles of innovation management of industrial enterprises in terms of analytical support of their product innovation policy.
Keywords: analytical support of planning; product innovation policy; transformation of technological systems; innovation management; industrial enterprises